Effect of Safety Management from Training of Safety Curriculum for Supervisors in a Food Production Company in Kamphaeng Phet Province - Julkaiwansutjar, Anan; Soontornchai, Sarisak; Lertwisuttipaiboon, Sudaw (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 4 (2019): October-December 2019, 2019)
The purposes of this quasi experimental research were: (1) to investigate the safety working condition problems and accident statistics in a food production company; (2) to explore safety attitude and safety behavior levels among supervisors in the company; (3) to compare knowledge before and after the safety training for supervisors in the company; and (4) to compare the effect of safety management by supervisors after training at the company in Kamphaeng Phet Province. The study samples were all 40 supervisors attending the safety training involving rotating machines for supervisors which this training curriculum assigned for in-house training.      The findings of this research indicated that: (1) the first accident priority of the company in 2017 was due to the hit/cut/nip frequently related with rotating machine working; (2) most supervisors had high level of safety attitudes, and very high level of safety behaviors; (3) average post-test score of supervisors was significantly higher than that of pre-test. (p < 0.05); and (4) one month monitoring of the working condition improvement indicated that supervisors had opinion about safety condition improvement at the very good level and the rotating machine guard condition had been investigated for safety machine working.  A total of 1,503 machines had been repaired by using the machine guard.   Keywords: Safety management, Safety training, Rotating machine